The use of 3D printing technology in prototypes of selected components for civil and military rail vehicles - Frankowski Maciej; Cichoński Zbigniew; Stępniewski Łukasz; Sawczuk Wojciech (2024)
The article discusses the Rapid Prototyping (RP) technology in the design of components of civil and military rail vehicles. The literature review has revealed a research niche in this area due to the specific requirements for these vehicles and a very narrow market. Because construction of those vehicles is mainly a manufacture, there is a risk of discrepancies between the 3D model, and the actual product. This issue has a significant impact on the design process, which is often associated with frequent changes during production. However, thanks to RP method, it is possible to refine designing component before it’s installation on the vehicle. This results in the aim of this work, namely to develop the concept of a roof vent for a rail vehicle as a confirmation of the thesis that the RP technology significantly accelerates and facilitates work in the designing of rail components. In order to solve the research problems posed, qualitative research methods were used. The analysis allowed two roof vent concepts to be tested simultaneously by designing it from interchangeable parts. In addition, thanks to the availability of plastics compliant with fire protection standard PN-EN 45545, a new type of vent has been designed strictly for 3D printing technology. This results with detail that would be technologically impossible to produce using conventional methods due to hardware limitations. One of the most important conclusions obtained after the research is the fact that this technology is not suitable for the production of large-size elements and serial production.